Teknik Estimasi Transpirasi Tanaman Kelapa Sawit dengan Metode Heat Ratio - Iput Pradiko; Nuzul Hijri Darlan; Eko Noviandi Ginting; Muhdan Syarovy (Jurnal Penelitian Kelapa Sawit, 2022)
The estimation of plant transpiration is one of many methods to determine plant water requirements. Heat Ratio Method (HRM) is a method that can estimate transpiration directly under field conditions by measuring sap flow rate. This research was conducted to estimate oil palm water requirements based on transpiration estimation using HRM. The study was located in Medan, North Sumatra, and was employed five years old palm with 48 fronds. A total of six Sap Flow Meter (SFM) were installed on the fronds no. 1, 9, 17, 25, 33, and 41. The results showed that the sap flow rate of the top three fronds (no. 1, 9, and 17) was higher than the lower fronds. The transpiration rate was decreased at the lower fronds position. Furthermore, the highest transpiration occurred in frond no. 1, 0.890 liters/day, while the lowest was observed in frond no. 41 i.e. 0.510 liters/day. Assuming that each frond sampled represents fronds at the same level, the average daily transpiration was 31.933 liters/day/palm or equivalent to 0.457 mm/day/palm.